Expression alterations define unique molecular characteristics of spinal ependymomas - Lourdusamy, Anbarasu; Rahman, Ruman; Grundy, Richard G. (Impact Journals, 2015)
Ependymomas are glial tumors that originate in either intracranial or spinal regions. Although tumors from different regions are histologically similar, they are biologically distinct. We therefore sought to identify molecular characteristics of spinal ependymomas (SEPN) in order to better understand the disease biology of these tumors. Using gene expression profiles of 256 tumor samples, we identified increased expression of 1,866 genes in SEPN when compared to intracranial ependymomas. These genes are mainly related to anterior/posterior pattern specification, response to oxidative stress, glial cell differentiation, DNA repair, and PPAR signalling, and also significantly enriched with cellular senescence genes (P = 5.5 × 10-03). In addition, a high number of significantly down-regulated genes in SEPN are localized to chromosome 22 (81 genes from chr22: 43,325,255 – 135,720,974; FDR = 1.77 × 10-23 and 22 genes from chr22: 324,739 – 32,822,302; FDR = 2.07 × 10-09) including BRD1, EP300, HDAC10, HIRA, HIC2, MKL1, and NF2. Evaluation of NF2 co-expressed genes further confirms the enrichment of chromosome 22 regions. Finally, systematic integration of chromosome 22 genes with interactome and NF2 co-expression data identifies key candidate genes. Our results reveal unique molecular characteristics of SEPN such as altered expression of cellular senescence and chromosome 22 genes.